DATA SECURITY SYSTEM ON THE APPLICATION OF REGIONAL INNOVATION INDEX IN INDONESIA - Ray Septianis Kartika (Proceedings of the 1st International Conference on Social Science (ICSS), 2023)
Regional innovations every year become mandatory for regions to report to the Ministry of Home Affairs. The reported data is recorded in the regional innovation index application. This application has been running for 6 years and has not yet realized a data security system that is able to protect every reported data. The problem is that this application is made by a third party that needs extra assistance by the Ministry of Home Affairs, the data that has been in the system is data that changes one after another because there are often changes or mutations of the implementing officials who handle it. Therefore, this study becomes urgent, to see the need for data inputted in the application and create a data security system model. The method is qualitatively through the spread of Goggle Form. The results of the study stated that this system is very helpful for local governments in mapping their innovations, and data security systems are offered there are four things, namely ISO / IEC 2700i standards, Filtering, Zero Trust Network and Cloud Security